2016
DOI: 10.3389/fendo.2016.00141
|View full text |Cite
|
Sign up to set email alerts
|

A Candidate Gene Association Study of Bone Mineral Density in an Iranian Population

Abstract: The genetic epidemiology of variation in bone mineral density (BMD) and osteoporosis is not well studied in Iranian populations and needs more research. We report a candidate gene association study of BMD variation in a healthy cross-sectional study of 501 males and females sampled from the Iranian Multi-Centre Osteoporosis Study, Shiraz, Iran. We selected to study the association with 21 single nucleotide polymorphisms (SNPs) located in the 7 candidate genes LRP5, RANK, RANKL, OPG, P2RX7, VDR, and ESR1. BMD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…Sassi et al [46] analyzed the association of other VDR polymorphisms (ApaI and TaqI) with BMD in postmenopausal Tunisian women and an increased risk to develop osteopenia, but not OP, was shown which strengthens the hypothesis that OP results from the interaction of genetic and environmental factors. The relationship of the 21 single nucleotide polymorphisms (SNP) in 7 selected candidate genes (LRP5, RANK, RANKL, ESR1, VDR, P2XR7, and OPG) with BMD at different body sites was evaluated in an Iranian population [47]. The overall pattern of association of these established risk SNPs were similar to those observed in other populations.…”
Section: Non-modifiable Risk Factors Modifiable Risk Factorsmentioning
confidence: 86%
“…Sassi et al [46] analyzed the association of other VDR polymorphisms (ApaI and TaqI) with BMD in postmenopausal Tunisian women and an increased risk to develop osteopenia, but not OP, was shown which strengthens the hypothesis that OP results from the interaction of genetic and environmental factors. The relationship of the 21 single nucleotide polymorphisms (SNP) in 7 selected candidate genes (LRP5, RANK, RANKL, ESR1, VDR, P2XR7, and OPG) with BMD at different body sites was evaluated in an Iranian population [47]. The overall pattern of association of these established risk SNPs were similar to those observed in other populations.…”
Section: Non-modifiable Risk Factors Modifiable Risk Factorsmentioning
confidence: 86%
“…Polymorphisms in OPG and RANKL have been associated with BMD or PMO in different genome-wide association studies derived from Europeans and East Asians [ 25 , 26 ]. The pathogenic mechanism of OPG and RANKL gene variants in osteoporosis development remains unclear since previous studies have reported contradictory findings [ 2 , 27 , 28 , 29 ]. The present study is the first to provide information on the association of RANKL and OPG gene polymorphism with osteoporosis phenotype in Saudi Arabian postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Выявлено несколько мутаций гена TNFSF11, одной из которых является поли-морфизм rs9594738 (C>T). К настоящему времени выполнено ряд исследований, направленных на изучение роли данного полиморфизма в форми-ровании остеопороза и возникновение переломов [7][8][9]11]. Однако полученные в них результаты имеют определенные противоречия.…”
Section: âведениеunclassified
“…Кроме того, они не выполняли денситометрию ко-стей предплечья. Исследование женщин и муж-чин, проживающих в Иране, также позволило об-наружить ассоциацию полиморфизма rs9594738 (C>T) гена TNFSF11 с МПК поясничных позвонков, но не бедренной кости [8].…”
Section: таблицаunclassified